Sistem Informasi Obat Masuk Dan Keluar Pada Rumah Sakit Airmas Chemical - Purnama Nababan; Ester Manullang (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Airmas Chemical Hospital Is a hospital that provides medicines. Data processing of incoming and outgoing drug supplies at the hospital is still simple by recording using Ms.Excel and MS.Word. This can make it difficult for officers if they want to check incoming and outgoing drugs, or see drug stocks in real time because there are many types of drugs available. The solution to this problem is to build a web-based drug inventory information system that is used to manage drug data at home. sick. Likewise with the Airmas Chemical Medan company based on inadequate facilities and infrastructure, not optimal in data processing which is still slow and there needs to be a new system. This problem is minimized by using existing technology to facilitate employee work, minimizing employee working time so that it is more effective and efficient. The technology that will be applied in the company is in the form of building an Information System for Incoming and Outgoing Drugs, which usually helps in processing data at the company and is also efficient in working time for employees.